Perancangan UI/ UX Untuk Website Kasir Toko Sembako Agung Berbasis Prototype Menggunakan Metode Design Thinking - Hafiz Rakan Pradiva; Sri Wahyuni; Ruly Dwi Arista (Jurnal Teknologi Informasi (JUTECH), 2025)
Toko Sembako Agung faces challenges in recording transactions that are still done manually, which has the potential to cause errors in calculating and managing stock. To overcome this problem, this study aims to design a user interface (Ui) and user experience (Ux) for a prototype-based cashier website using the Design Thinking method. The Design Thinking method is applied through five main stages, namely Empathize, Define, Ideate, Prototype, and Test. In the Empathize stage, observations and interviews were conducted with users, namely cashiers and shop owners, to understand the needs and obstacles faced. The results of the study show that the application of the Design Thinking method in designing UI/UX is able to produce a cashier system design that is more user-friendly, efficient, and easy to use. This cashier website has main features such as transaction recording, stock management, and sales report generation. Testing of the prototype shows that the designed system can increase transaction efficiency and reduce recording errors compared to the manual method. Thus, UI/UX design based on the Design Thinking method can be an effective solution in developing a more optimal cashier system for grocery stores. Recommendations for further research are to develop this prototype into a system integrated with a real-time database and improve the security aspects of transaction data.